Associations of milk, dairy products, calcium and vitamin D intake with risk of developing Parkinson´s disease within the EPIC4ND cohort - Gröninger, Mareike; Sabin, Jara; Kaaks, Rudolf; Amiano, Pilar; Aune, Dagfinn; Castro, Natalia Cabrera; Guevara, Marcela; Hansen, Johnni; Homann, Jan; Masala, Giovanna; Nicolas, Geneviève; Peters, Susan; et al. (European journal of epidemiology, 2024)
Literature indicates a potential association between dairy consumption and risk of Parkinson´s disease (PD), especially among men, yet the results remain inconclusive. We investigated this association in a large prospective European cohort. Dietary and non-dietary data was collected from 183,225 participants of the EPIC-for-Neurodegenerative-Diseases (EPIC4ND) cohort, a sub-cohort of the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Crude and multivariable-adjusted Cox proportional hazards models were employed to examine potential associations between baseline dietary intake of dairy, calcium and vitamin D with incident PD risk. No relationship was observed between dairy consumption (HR 1.07, 95% CI 0.82-1.39), individual dairy products (milk: HR 0.95, 95% CI 0.73-1.23; yogurt: HR 1.03, 95% CI 0.82-1.29; cheese: HR 1.13, 95% CI 0.85-1.51), or vitamin D (HR 1.08, 95% CI 0.80-1.45) with PD risk. However, we observed a risk-increasing association with higher calcium intakes (HR 1.33, 95% CI 1.00-1.78, p for trend = 0.031), which was more pronounced in men (HR 1.50, 95% CI 1.00-2.25, p for trend = 0.044) and in ever smokers (HR 1.64, 95% CI 1.06-2.53, p for trend = 0.014). No compelling evidence was found for an association between dairy products or vitamin D intake and PD risk indicating a potentially limited relevance of dairy intake in PD risk than previously described. Our observations of a positive association between dietary calcium intake and PD risk in men and in ever smokers require further validation.
Online veröffentlicht: 3. Dezember 2024
Gesehen am 28.04.2025